Evidências no uso da fototerapia convencional em neonatos com icterícia - Juliana Tome Pereira (2009)
Neonatal ictericy is characterized by a yellowish tone in the skin and in the scleral ofnew born babies (NB) a termo bem como os pré e pós-termo and its frequentlypresent in the neonatal period, compromising between half and two thirds of newborn babies. It is characterized by elevated levels of indirect bilirrubin (IB) or nonconjugatedbilirrubin in a serum concentration superior to 1,5 mg/dl. This study is asystematic review on the efficient use of conventional fototherapy to reduce indirectbilirrubin in the new born babies who suffer from pathological ictericy. The objectivewas to highlight the procedures when using conventional fototherapy in the treatmentof pathological ictericy in new born babies in scientific publications of the clinical testrandomly controlled type. The sample was composed by nine articles published ineight international journals, all in English, from 2008 to February, 2009. It isrecommended the use of fluorescent and blue lights associated, preferably fourfluorescent lights and four blue lights or three fluorescent lights and two blue lights.Although the results allow making recommendations, it is important to do newresearch, with a bigger sample calculated before hand, to improve the knowledgeabout the procedures, besides identifying the undesirable consequences offototherapy and the ways to prevent them.